Are Strong Unions Compatible with the New Model of Human Resource Management ? - Wells, Don (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
It is widely argued that recent Human Resource Management (HRM) innovations are compatible with, indeed require, strong unions. This paper examines several cases which, it has been argued, illustrate the compatibility of strong unions and HRM reforms. The author concludes that, on the contrary, each case illustrates the incompatibility of HRM and strong unions and explains why this is so.